2012
DOI: 10.1177/0018726712451762
|View full text |Cite
|
Sign up to set email alerts
|

The problem-solving service worker: Appraisal mechanisms and positive affective experiences during customer interactions

Abstract: Affective Events Theory suggests customer interactions elicit event appraisals that, in turn, prompt affective reactions in employees. A qualitative diary study was used to examine the daily events and cognitive appraisals that elicit positive emotions during customer service interactions. Thematic analysis of the diary contents of 276 sales employees from a variety of industries (874 positive events) showed helping customers solve their problem was the event most likely to trigger positive emotions. The data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 71 publications
2
36
0
1
Order By: Relevance
“…Through deep acting, employees either persevere resources by avoiding a discrepancy between the felt and expressed emotion, and stay energetic (Hülsheger & Schewe, ), or they gain resources by sustaining positive social interactions at work (Brotheridge & Lee, ; Côté, ; Grandey, ) that help them to become absorbed in their work, to enjoy it, and to carry it out for the intrinsic pleasure of it. It should be noted that even when confronted with an angry customer, using deep acting to express the positive emotions (e.g., calmness) that are required by the organization may facilitate problem‐solving behaviors that eventually turn the interaction with the client into a positive experience (e.g., Kiffin‐Petersen, Murphy, & Soutar, ). Although deep acting related to need for recovery via both reduced exhaustion and increased flow, surface acting related to need for recovery only through high levels of exhaustion‐the indirect effect from surface acting to need for recovery via flow was very small and only marginally significant.…”
Section: Discussionmentioning
confidence: 99%
“…Through deep acting, employees either persevere resources by avoiding a discrepancy between the felt and expressed emotion, and stay energetic (Hülsheger & Schewe, ), or they gain resources by sustaining positive social interactions at work (Brotheridge & Lee, ; Côté, ; Grandey, ) that help them to become absorbed in their work, to enjoy it, and to carry it out for the intrinsic pleasure of it. It should be noted that even when confronted with an angry customer, using deep acting to express the positive emotions (e.g., calmness) that are required by the organization may facilitate problem‐solving behaviors that eventually turn the interaction with the client into a positive experience (e.g., Kiffin‐Petersen, Murphy, & Soutar, ). Although deep acting related to need for recovery via both reduced exhaustion and increased flow, surface acting related to need for recovery only through high levels of exhaustion‐the indirect effect from surface acting to need for recovery via flow was very small and only marginally significant.…”
Section: Discussionmentioning
confidence: 99%
“…It would be insightful to understand how cognitive appraisals of daily uplifts are configured and which are more likely to influence positive affect and work engagement in organizations. For instance, some cognitive appraisals considered as relevant, such as an agency or an event's importance (e.g., Kiffin-Petersen et al 2012) could be included in the analysis in order to understand when they lead employees to feel positive affect and more vigor, dedication and absorption at work. Hence, it could help understand better how and when daily uplifts influence employees' well-being and performance.…”
Section: Limitations and Future Researchmentioning
confidence: 99%
“…Extending the focus from "how the event feels" to "what it means" questions the common practice of coding work events into unitary positive or negative events (Ohly & Schmitt, 2015), as this practice assumes that all forms of the positive (or negative) events share a uniform influence on individuals (Ohly & Schmitt, 2015). On the other hand, research has found that different positive work events may have diverse effects-for example, in reducing stress or generating emotions (e.g., De Jonge & Dormann, 2006;Kiffin-Petersen, Murphy, & Soutar, 2012). Recent research on work events taxonomy has also suggested that a nuanced focus on differentiated events is more informative for the development of pertinent propositions (Ohly & Schmitt, 2015).…”
mentioning
confidence: 99%